2017
DOI: 10.1080/14686996.2017.1344929
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of cross-linked chitosan composites functionalised with silver and gold nanoparticles for antimicrobial applications

Abstract: We present a study of a range of cross-linked chitosan composites with potential antimicrobial applications. They were formed by cross-linking chitosan and siloxane networks and by introducing silver and gold nanoparticles (NPs). The aim was to investigate whether adding the metal NPs to the chitosan-siloxane composite would lead to a material with enhanced antimicrobial ability as compared to chitosan itself. The composites were synthesised in hydrogel form with the metal NPs embedded in the cross-linked chit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 59 publications
2
28
0
Order By: Relevance
“…Biopolymeric nanocomposites decorated with a metallic nanophase are advanced functional materials. The design and preparation of these advanced systems have one main purpose-the improvement and stabilization of the biostatic or antibacterial properties [39][40][41][42]. However, the cytotoxicity of the nanocomposites should also be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Biopolymeric nanocomposites decorated with a metallic nanophase are advanced functional materials. The design and preparation of these advanced systems have one main purpose-the improvement and stabilization of the biostatic or antibacterial properties [39][40][41][42]. However, the cytotoxicity of the nanocomposites should also be considered.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, CS composites with different materials such as metals and metal oxides have been produced, which because of the synergistic effect of constituents show excellent and improved properties . In this regard, CS and TiO 2 composites have recently attracted more attention and due to their excellent antibacterial characteristics in comparison with individual constituents, they have been using in the production of antibacterial products including novel antibacterial coatings …”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the antimicrobial efficacy of NPs has improved with the development of green synthesis methods. It has even been suggested that this is the result of the inherent bactericidal activity of natural sources combined with NPs [131]. In this respect, Khan et al [132] obtained AuNPs from the aqueous extract of Acer pentapomicum leaves, which was used as a reducing and stabilizing agent.…”
Section: Antibacterialmentioning
confidence: 99%